Marine endophytes: biosynthetic engines for novel bioactive metabolites - Kong, Cun-Cui; Wang, Jia-Yi; Shan, Bo-Hao; Zhang, Hong-Xia; Qin, Song; Ren, Cheng-Gang (Frontiers in Microbiology, 2025)
Marine endophytes are prolific sources of structurally diverse secondary metabolites with significant pharmaceutical potential, including anticancer, antimicrobial, and antioxidant agents. However, their commercial utilization is hindered by genomic instability in axenic cultures and inconsistent metabolite yields. While current studies focus on symbiotic interactions and compound discover, critical gaps persist in harnessing their biosynthetic capabilities. This review synthesizes knowledge on marine fungal metabolites and proposes a paradigm shift toward resource-driven research. It addresses strain improvement limitations and suggests strategies like mutagenesis, protoplast fusion, and metabolic engineering to bolster production stability and efficiency. The paper also discusses biological process optimization, including fermentation tuning, inducer and precursor addition, and adsorbent use, to enhance natural product synthesis. By identifying these research gaps and proposing a strategic roadmap, the review advances the stable and scalable production of bioactive metabolites, unlocking the commercial and therapeutic potential of marine endophytic fungi.